(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
Study the history of the vocabulary of the Ukrainian language is impossible without finding Formation of separate groups of semantic lexicon, in particular kolorativov. The article deals with the composition and characteristics of functioning in old Ukrainian language colour name (XI–XIV cent.).